Simultaneous Electroencephalographic and Electocorticographic Recordings of Lateralized Periodic Discharges in Temporal Lobe Epilepsy. (January 2022) - Sakata, Ayumi; Mukae, Nobutaka; Morioka, Takato; Tanaka, Shunya; Shimogawa, Takafumi; Shigeto, Hiroshi; Hotta, Taeko; Kang, Dongchong; Mizoguchi, Masahiro
Objective: Lateralized periodic discharges (LPDs), which constitute an abnormal electroencephalographic (EEG) pattern, are most often observed in critically ill patients with acute pathological conditions, and are less frequently observed in chronic conditions such as focal epilepsies, including temporal lobe epilepsy (TLE). Here we aim to explore the pathophysiological mechanism of LPD in TLE. Methods: We retrospectively selected 3 patients with drug-resistant TLE who simultaneously underwent EEG and electrocorticography (ECoG) and demonstrated LPDs. We analyzed the correlation between the EEG and ECoG findings. Results: In patients 1 and 2, LPDs were recorded in the temporal region of the scalp during the interictal periods, when repeated spikes followed by slow waves (spike-and-wave complexes; SWs) and periodic discharges (PDs) with amplitudes of >600 to 800 µV appeared in the lateral temporal lobe over a cortical area of >10 cm 2 . In patient 3, when the ictal discharges persisted and were confined to the medial temporal lobe, repeated SWs were provoked on the lateral temporal lobe. When repeated SWs with amplitudes of >800 µV appeared in an area of the lateral temporal lobe of >10 cm 2, the corresponding EEG discharges appeared on the temporal scalp. Conclusions: LPDs in patients with TLE originate from repeated SWs and PDs of the lateral temporal lobe, which might represent a highly irritable state of the lateral temporal cortex during both interictal and ictal periods.